(untitled) (Journal of Health Sciences, 2017)
Introduction: The aim of the study was to evaluate quality of life (QoL) in patients with colorectal cancer (CRC) during complex treatment using the European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30 and QLQ-CR29 questionnaires and to implement routine QoL assessment into our practice. Methods: 30 patients diagnosed with CRC at the Department of Surgery, Faculty Hospital Trnava, Slovakia were included in the study between May 2014 and April 2015. QoL was assessed using EORTC QLQ-C30 and QLQ-CR29 questionnaires before surgery and 1 month after surgery. Data are presented as means, and a paired t-test and independent t-test were used for statistical analysis. Results: A significant correlation between the type of treatment and QoL was identified in the cohort. A trend to lower QoL was observed in patients with completed neoadjuvant chemoradiotherapy (CRT) and after surgery with stoma formation. The QoL was also affected by the age and gender of the patients. Conclusion: QoL assessment provides important outcomes reflecting the consequences of particular therapeutic modality in patients with CRC. The worse effect of neoadjuvant CRT and stoma formation was shown in our study in comparison to radical resection with adjuvant chemotherapy.